Awakening is not a metaphor: the effects of Buddhist meditation practices on basic wakefulness. (26th December 2013) - Britton, Willoughby B.; Lindahl, Jared R.; Cahn, B. Rael; Davis, Jake H.; Goldman, Roberta E.
Abstract : Buddhist meditation practices have become a topic of widespread interest in both science and medicine. Traditional Buddhist formulations describe meditation as a state of relaxed alertness that must guard against both excessive hyperarousal (restlessness) and excessive hypoarousal (drowsiness, sleep). Modern applications of meditation have emphasized the hypoarousing and relaxing effects without as much emphasis on the arousing or alertness‐promoting effects. In an attempt to counterbalance the plethora of data demonstrating the relaxing and hypoarousing effects of Buddhist meditation, this interdisciplinary review aims to provide evidence of meditation's arousing or wake‐promoting effects by drawing both from Buddhist textual sources and from scientific studies, including subjective, behavioral, and neuroimaging studies during wakefulness, meditation, and sleep. Factors that may influence whether meditation increases or decreases arousal are discussed, with particular emphasis on dose, expertise, and contemplative trajectory. The course of meditative progress suggests a nonlinear multiphasic trajectory, such that early phases that are more effortful may produce more fatigue and sleep propensity, while later stages produce greater wakefulness as a result of neuroplastic changes and more efficient processing.